Peran Ibu Terhadap Pendidikan Anak dalam Novel Layangan Putus Perspektif Pendidikan Islam - Mariaty Podungge (Pedagogik Journal of Islamic Elementary School, 2021)
The purpose of the study was to analyze the role of mothers in children’s education in the novel Layangan Putus from an Islamic education perspective.  In the novel, Mother has five children: Amir, Arya, Alman, Abi, and Ahmad.  Ahmad died when he was born to his mother.  So child care focuses on their four children.  In educating children, mothers experience a change in status from wife to widow.  Education for children that were previously carried out with the father, according to the results of the divorce court decision, that custody rests with the mother.  Therefore, researchers want to know the role of the mother in educating children from an Islamic education perspective.  This type of research is library research.  Data collection is done by doing repeated readings and documentation.  Analysis of the data used is content and comparative analysis.  The results showed that (1) the mother continued to practice her nature as an educator even though she worked as a veterinarian, and (2) the mother was responsible for faith education, moral education, physical education, academic education, mental education, and children’s social education.